2010
DOI: 10.1142/s0217751x10048524
|View full text |Cite
|
Sign up to set email alerts
|

A Minimal Model of Lorentz Gauge Gravity With Dynamical Torsion

Abstract: A new Lorentz gauge gravity model with R 2 -type Lagrangian is proposed. In the absence of classical torsion the model admits a topological phase with an arbitrary metric. We analyze the equations of motion in constant curvature space-time background using the Lagrange formalism and demonstrate that the model possesses a minimal set of dynamic degrees of freedom for the torsion. Surprisingly, the number of torsion dynamic degrees of freedom equals the number of physical degrees of freedom for the metric tensor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 30 publications
(21 reference statements)
1
24
0
Order By: Relevance
“…It has been shown that the model described by the Lagrangian (13) admits dynamical degrees of freedom for the contortion only for the special values of the parameters, ¼ 0, ¼ À3 with overall normalization factor [13]. The result has been obtained from the analysis of linearized equations of motion for contortion in the presence of constant Riemann curvature space-time background.…”
Section: Lorentz Gauge Theory With Topological Gravitymentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that the model described by the Lagrangian (13) admits dynamical degrees of freedom for the contortion only for the special values of the parameters, ¼ 0, ¼ À3 with overall normalization factor [13]. The result has been obtained from the analysis of linearized equations of motion for contortion in the presence of constant Riemann curvature space-time background.…”
Section: Lorentz Gauge Theory With Topological Gravitymentioning
confidence: 99%
“…If the contortion still possesses dynamical properties in flat space-time, then another important question arises, at which values of the parameters , , it will happen. In the present paper, we will mainly concentrate on flat metric limit, i.e., a pure Lorentz gauge theory with the Lagrangian of type (13). The field strength (curvature tensor) in flat space-time takes a simple form…”
Section: Lorentz Gauge Theory With Topological Gravitymentioning
confidence: 99%
See 3 more Smart Citations